Caracterização epidemiológica do mormo em equídeos no Estado da Paraíba com base em dados secundários - Rosado, Felipe (2018)
Glanders is a disease that affects equidae and eventually other animal species, including humans, characterized by severe zoonosis. The Agricultural Defense of the State of Paraíba in the fulfillment of its attributions works in control applying the established in federal legislation. Thus, many animals are slaughtered and destroyed every year without the data obtained being used in order to characterize the disease epidemiologically in Paraiba territory. Therefore, the purpose of this study was to characterize the geographic distribution of the disease in the State, identify the main equidae species affected, as well as the age group, the races and the sex most affected. Data from the archives of the Official Veterinary Service of the state of Paraíba from January 2013 to December 2017 were used. The results are of 268 equidae tested, of which 41 were positive. Of these, only six presented clinical symptoms, distributed in 34 municipalities of the State, ranging from 10 months to 20 years, of both sexes, with Quarter Horse, Paint Horse, undefined and mixed race animals. There were animals of the equine, muar and asinine species. The event that triggers examination for glanders is the need for a certificate with a negative result in order to obtain the Animal Transit Guide - ATG when the purpose of the movement demands it, which is the case of sporting events with agglomerations of animals and transportation to other states, so most of the animals tested were of the equine and Quarter Horse species. For the same reason age could not be considered as interfering or not in susceptibility to disease. There was no significant difference between sex.